Evaluación del sistema de tratamiento de aguas residuales del complejo urbanístico Barcelona de Indias (2015)
The work developed presents the evaluation of the operation of the domestic wastewater treatment system of the urban complex Barcelona de Indias. A description was made of each one of the components of the plant to understand its operation since there are no plans or calculation memories or technical specifications. Figure 1 shows an original outline of each of the PTARD parts. It shows that in the last inspection well of the sewerage network of the urbanization begins the operation of the treatment plant. In this well a submersible pump is located that sends the flow to the equilibrium tank where submersible pumps are available that send a constant flow to the reactor. The reactor is divided into four modules where air is injected by means of compressors and sludge is recirculated. The effluent is sent by gravity to the lake. The poor condition of the components of the WWTP was determined due to: pumps operating with inconstant flow rates, poor maintenance, compressor pipes with a smaller diameter than what was proposed by the manufacturer, in carbon steel, oxidized and inactive; disarmed recirculation pumps and there is no recirculation of flow and sludge to the reactor. Samples were taken from the effluent and effluent of the treatment plant between July 15 and 23, 2013, analyzed in the laboratory and evaluated taking into account the parameters established in the Colombian regulations for the treatment and discharge of wastewater according to the decree. 1594 of 1984, valid for the time of the study.